The Narrator’s Perspective in True Crime: The Case of the Urban Guard in TV3 and Netflix Productions - Sánchez Esparza, Marta; Méndiz, Alfonso (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
True crime is currently experiencing significant fervor and controversy due to its ethical implications, particularly concerning the narrator's authority. This article examines how new and varied true crime narrators alter audience perceptions of recounted events. Employing a threefold methodology—historical context, comparative analysis of three narrations of the same case, and interviews with creators—the study focuses on the urban guard crime in Barcelona. Analyzed productions include TV3's Crims, Netflix's docuseries Las cintas de Rosa Peral, and the fictional series El cuerpo en llamas. The findings test a proposed typology of narrators, revealing how narrative choices influence audience perception and emotional response.